2014
DOI: 10.1016/j.exger.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking phenotype and production of granzyme B by double negative B cells (IgG+IgD−CD27−) in the elderly

Abstract: The impairment of humoral immune response in elderly humans has been extensively demonstrated. We have reported the increase of memory B cells (IgG, double negative, DN) population in the elderly, in which there is also a typical inflammatory micro-environment. In order to evaluate whether this pro-inflammatory status could influence the trafficking phenotype of naïve/memory B cells, we have assessed the expression of CCR7, CCR6, CXCR3, CXCR4, CXCR5 and CD62L on naïve/memory B cell subpopulations in young and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 59 publications
(91 reference statements)
2
42
0
Order By: Relevance
“…This was due to the increased expression of Granzyme B and FasL in IL-17A-treated B cells. Our results are consistent with previous findings that there is a subpopulation of B cells which could be stimulated to produce Granzyme B [32]. Besides, Hahne et al reported that activated B cells could express FasL, which were able to kill Fas-sensitive target cells [33].…”
Section: Discussionsupporting
confidence: 93%
“…This was due to the increased expression of Granzyme B and FasL in IL-17A-treated B cells. Our results are consistent with previous findings that there is a subpopulation of B cells which could be stimulated to produce Granzyme B [32]. Besides, Hahne et al reported that activated B cells could express FasL, which were able to kill Fas-sensitive target cells [33].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed although DN B cells are less responsive, some particular conditions (i.e. IL-21 + ␣-IgG) can activate them [60] as demonstrated by their ability to produce Granzyme B that act against viruses or cancer cells [61,62]. Finally, the data on the expression of the inhibitory receptors CD307d and CD22 suggest that DN cells are not fully comparable to other B cell populations described in old or chronically stimulated mice and humans [23,24].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, it has been reported in humans that granzyme B + B cells accumulated specifically in tissues and have been suggested to play a critical role in early antiviral immune responses, in the regulation of autoimmune mechanisms, and in cancer immunosurveillance (45)(46)(47). Additionally, it has recently been shown that BCR and IL-21 signaling without an efficient CD40-CD40L ligation leads to the generation of granzyme B + B cells that induce immune dysfunction in solid tumor eradication (45,(48)(49)(50) or in HIV patients (51).…”
Section: Igmmentioning
confidence: 99%